Three-dimensional imaging methods to quantify soft and hard tissues change after cleft-related treatment during growth in patients with cleft lip and/or cleft palate: a systematic review - Awarun, Bennaree (Dentomaxillofac Radiol, 2018)
OBJECTIVES: To assess the use of three-dimensional (3D) imaging methods to quantify the changes in soft- and hard-tissues in cleft patients after cleft-related treatment during growth. METHODS: PubMed, EMBASE, Web of Science and the Cochrane Library were searched up to 1 June 2018. Included publications were those using 3D imaging to quantify soft- and hard-tissue changes after cleft-related treatments in patients with any type of cleft, during growth. Data extraction and qualitative analysis were performed by two reviewers. The methodological quality of each study was reviewed using the QUADAS-2 tool. RESULTS: From 4 databases, 2315 articles were found. Full texts of 422 articles were analyzed and finally 12 articles were included for qualitative analysis. CT was performed in the majority of studies for hard-tissue quantification. Stereophotogrammetry, Laser scanner and 3D digitizer were identified as viable methods to quantify both soft- and hard-tissue changes, depending on whether the scan was made of the facial surface or the cast surface. Most studies conducted imaging analysis without registration between multitemporal images, which is the reason why they did not fulfil the inclusion criteria. CONCLUSIONS: Although several imaging modalities have the potential to quantify cleft-related treatment follow-up, there is an urgent need to assess the imaging methods and related analyses allowing to standardise a 3D imaging protocol to quantify hard- and soft-tissue treatment follow-up.